2005
DOI: 10.4000/bifea.4880
|View full text |Cite
|
Sign up to set email alerts
|

Espacio social y áreas de actividad en asentamientos agrícolas prehispánicos tardíos en la sierra de Arica*

Abstract: El presente trabajo tiene como objetivo discutir el espacio social generado en tres de los mayores asentamientos prehispánicos ubicados en la sierra de Arica, sobre los 3 000 msnm, extremo norte de Chile: Huaihuarani, Lupica y Saxamar. La discusión está centrada en el análisis de una serie de áreas de actividad que se generaron tanto al interior de los recintos habitacionales como fuera de ellos, así como: terrazas de cultivos, caminos, plazas, corrales, enterramiento, pozos de almacenajes y los componentes ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…(). For this reason, we mostly worked with a relative chronology, used by archaeologists in different regions of the Americas (Erickson, ; Treacy, ; Quesada, ; Muñoz Ovalle, ; Albeck, ; Cruz, among others). In this sense, elements such as the preeminence of Aguada pottery in the area, the similarity between the surveyed households and those located on the valley floor, the recurrent spatial arrangement of the different types of buildings and the similarity noticed in the raw materials and construction techniques used, allowed us to assign them to the period of Aguada occupation of the valley, between 300 and 1000 ad .…”
Section: Introductionmentioning
confidence: 99%
“…(). For this reason, we mostly worked with a relative chronology, used by archaeologists in different regions of the Americas (Erickson, ; Treacy, ; Quesada, ; Muñoz Ovalle, ; Albeck, ; Cruz, among others). In this sense, elements such as the preeminence of Aguada pottery in the area, the similarity between the surveyed households and those located on the valley floor, the recurrent spatial arrangement of the different types of buildings and the similarity noticed in the raw materials and construction techniques used, allowed us to assign them to the period of Aguada occupation of the valley, between 300 and 1000 ad .…”
Section: Introductionmentioning
confidence: 99%
“…Many Chilean archaeologists reporting on regional settlement surveys now include descriptions of the ''use of space'' in which they detail the residential and nonresidential components of sites and classify the forms of domestic structures, often contrasting between rounded and rectilinear buildings and associating different forms with groups of altiplano, sierra, or coastal origins (e.g., Adán et al 2007;Chacama 2005;Muñoz Ovalle 2005). Style of masonry and form of domestic space also have been used to infer differences between Inka and support staff on royal estates in the Sacred Valley of Cuzco (Niles 1987) or to identify similar differences at provincial centers (Morris and Thompson 1985, p. 70).…”
Section: Ethnohistoric Models Of Coresidential Groupsmentioning
confidence: 98%
“…The architecture itself is a major factor from which archaeologists have inferred the size and organization of coresidential groups (e.g., Malpass and Stothert 1992;Muñoz Ovalle 2005). Compounds or enclosures including several house units are interpreted very differently from dispersed residential structures within unbounded or nondemarcated communities.…”
Section: Residence and Social Organizationmentioning
confidence: 99%
“…A recent study on settlement patterns since the twelfth century AD in the Arica Precordillera identifies several villages that were established near to agricultural productive areas (Saintenoy et al, 2017). Furthermore, the authors emphasized a strong farming imprint around the three previously identified large agricultural localities (Muñoz Ovalle, 2005). Evidence of small settlements with 2 to 5 circular structures of less than 7 m in diameter were identified (Saintenoy et al, 2017), linked both to agricultural practices and livestock.…”
Section: Implications For Regional Human Settlementmentioning
confidence: 99%
“…The transition towards the Formative or Neolithic Andean in the region was so gradual that until at least 1400 yr it is not possible to observe significant changes in the way of life of these high-Andean populations (Sepúlveda et al, 2018). This gradual transition occurs despite interactions with other sedentary groups; potters, farmers, and pastoralists that were settled in neighboring regions (Sepúlveda et al, 2018).From the twelfth century AD onwards, large settlements indicate a novel usage of the Precordillera, related to significant agricultural and pastoral practices requiring a strong sedentary imprint formed around three principal localities with considerable farming practices in the surrounding areas (Muñoz Ovalle, 2005). Farms are related to the presence of terraces and corrals for hosting domesticated camelids (Saintenoy et al, 2017).…”
Section: Human Occupationmentioning
confidence: 99%